Stressors and Their Association with Symptoms of Depression, Anxiety and Stress in Dental Students - Radeef, Ali S; Faisal, Ghasak G (Makara Journal of Health Research, 2018)
Background: Dental students are exposed to varying levels of stress that may affect their mental and physical health, academic performance and quality of life. This study aim was to determine the prevalence and severity of depression, anxiety and stress (DAS), and the relationships between DAS symptoms and stressors. Methods: This cross-sectional study included 257 dental students at the International Islamic University Malaysia. The prevalence and severity of DAS symptoms was measured by the Depression, Anxiety, Stress Scale (DASS-21). The stressors were self-reported by students from a list, and the relationships with the DAS symptoms were assessed. Results: The overall prevalence of DAS symptoms for depression, anxiety, and stress were 47.5%, 67.3% and 42.8%, respectively. Clinically significant depression was experienced by 9.3% of the students, anxiety by 28.8% and stress by 10.1%. Anxiety was significantly more frequent in women than in men, and anxiety scores were significantly increased in young students. The top five stressors were time management problems, fear of failing, examination and low grades; feeling of incompetence and study pressure. Conclusions: DAS symptoms occurred in dental students. Academic and personal factors produced stress that precipitated psychological distress.